2016
DOI: 10.1007/s10072-016-2643-5
|View full text |Cite
|
Sign up to set email alerts
|

The interplay of microRNAs and post-ischemic glutamate excitotoxicity: an emergent research field in stroke medicine

Abstract: Stroke is the second leading cause of death and the most common cause of adult disabilities among elderlies. It involves a complex series of mechanisms among which, excitotoxicity is of great importance. Also, miRNAs appear to play role in post-stroke excitotoxicity, and changes in their transcriptome occur right after cerebral ischemia. Recent data indicate that specific miRNAs such as miRNA-223, miRNA-181, miRNA-125a, miRNA-125b, miRNA-1000, miRNA-132 and miRNA-124a regulate glutamate neurotransmission and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 79 publications
0
19
0
Order By: Relevance
“…In recent years, growing evidence has suggested that microRNAs (miRNAs) play critical roles in ischemic stroke [11]. Experimental therapeutic approaches based on miRNAs have been developed to help post-stroke neurological recovery and ameliorate ischemic brain injury [12,13]. miR-29b-3p, one of the members of the miR-29b family to be identified, exhibits therapeutic potential for treating cardiometabolic disorders [14].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, growing evidence has suggested that microRNAs (miRNAs) play critical roles in ischemic stroke [11]. Experimental therapeutic approaches based on miRNAs have been developed to help post-stroke neurological recovery and ameliorate ischemic brain injury [12,13]. miR-29b-3p, one of the members of the miR-29b family to be identified, exhibits therapeutic potential for treating cardiometabolic disorders [14].…”
Section: Introductionmentioning
confidence: 99%
“…Intriguingly, in nonischemic animals, DIM upregulated the expression of miR-223-3p involved in Grin2b degradation as well as increased methylation of Grin2b gene which links DIM to the control of excitotoxicity [41]. Moreover, in nonischemic rats, DIM stimulated expression of miRNAs such as miR-124, miR-384, and miR-181b, which are related to apoptosis, autophagy and/or excitotoxicity [42,43]. Similarly, re-expression of miRNAs in response to DIM was demonstrated in cancer cell lines [44].…”
Section: Discussionmentioning
confidence: 97%
“…By being the second most frequent mortality cause and also the first leading cause of adult disabilities, stroke is taking its toll in all over the world. 1 In tandem with its global trend, the stroke prevalence was demonstrated to be very high in Iran by involving approximately 139 per 100 000 cases in 2006. 2 The main mechanisms are disruption of cerebral blood flow and hypo-oxygenation, by which brain tissue is affected during an ischemic attack.…”
Section: Introductionmentioning
confidence: 99%